FANDOMS AND LEARNING: THE ROLE OF ACA-FANS IN FORMAL EDUCATION - Castilho, Fernanda; de Marques Tavares, Enoe Lopes Pontes (AoIR Selected Papers of Internet Research, 2026)
This article examines the role of fandoms and aca-fan communities within the contexts of formal and informal education. Drawing on the notion of lifelong learning (Jarvis, 2004), we investigate how fan practices—including content production, community organization, critical engagement, and the circulation of knowledge—can contribute to academic, technical, and professional learning processes. Based on these premises, we formulate the central question of this research: can participation in fandoms support formal learning? Our objective is to understand how fan practices, particularly among aca-fans, are transformed into academic and professional repertoires.